Psycho-pedagogical characterization of the process of initiation in chess from the perspective of the basic elements/Caracterización psicopedagógica del proceso de iniciación en ajedrez desde la perspectiva de los elementos básicos - Gonzalo Giraldo García Camejo; Maikel Tejeda Piñeiro; Lexy Figueredo Frutos; Francisco Núñez Aliaga (Podium, 2022)
The research was directed towards the process of chess sports initiation during the period of general basic training, with the objective of characterizing this process from psycho-pedagogical criteria during the teaching-learning of the basic elements of this sport discipline; therefore, its importance lay in the contribution to the special didactics of chess, by giving it a formative, contextualized and logical sequential character in search of the general basic training of schoolchildren from an integral educational approach. In addition, from the theoretical renovation, it is possible to conceive a dialectic and global sport initiation in order to enable the schoolchildren and educator to acquire resources such as knowledge, skills and attitudes